Assessment of left ventricular 2D flow pathlines during early diastole using spatial modulation of magnetization with polarity alternating velocity encoding: A study in normal volunteers and canine animals with myocardial infarction. Issue 3 (8th October 2012) - Zhang, Ziheng; Friedman, Daniel; Dione, Donald P.; Lin, Ben A.; Duncan, James S.; Sinusas, Albert J.; Sampath, Smita
<x xml:space="preserve">Abstract</x> A high‐temporal resolution 2D flow pathline analysis method to study early diastolic filling is presented. Filling patterns in normal volunteers (n = 8) and canine animals [baseline (n = 1) and infarcted (n = 6)] are studied. Data are acquired using spatial modulation of magnetization with polarity alternating velocity encoding, which permits simultaneous quantification of 1D blood velocities (using phase contrast encoding) and myocardial strain (using spatial modulation of magnetization tagging and harmonic phase analysis) at high‐temporal resolution of 14 ms within a single breath hold. Virtual emitter particles, released from the mitral valve plane every time frame during rapid filling, are tracked to depict the 2D pathlines on the imaged plane. The pathline regional distribution is compared with myocardial longitudinal strains and to regional pressure gradients. Quantitative analysis of net kinetic energy of pathlines is finally performed. Our results demonstrate a linear correlation (r2 = 0.85) between pathline spatial distribution and myocardial strain. Peak net kinetic energy of 0.06 ± 0.01 mJ in normal volunteers, 0.043 mJ in baseline dog, 0.143 ± 0.03 mJ in infarcted dogs with nominal flow dysfunction, and 0.016 ± 0.007 mJ in infarcted dogs with severe flow dysfunction is observed. In conclusion, 2D pathline analysis provides a direct regional assessment of early diastolic filling patterns and is sensitive to abnormalities in early diastolic filling. Magn Reson Med 70:766–775, 2013. © 2012 Wiley Periodicals, Inc.